Andalusia, from Peripheral Urbanism to Real-State Bubble. Hiperdevelopment of Real-State Sector as Sign of Underdevelopment - Díaz-Parra, Ibán; Romano, Silvina (Revista de Estudios Andaluces, 2016)
Andalusia has been historically a peripheral area within European capitalism. This paper aims to present the actuality of this situation changing the usual focus, from the study of rural issues to the production of space. In order to do this, some theoretical aspects regarding peripheral urbanism and the theory of the second circuit of capital accumulation of Henry Lefebvre and David Harvey will be discussed. These models will be compared with the case of Andalusia, considering secondary sources and public statistics data about social and economic structure. Finally, the paper concludes that in the transition from a commodity-export pattern to another one based in the articulation between tourism and real-estate bubble, Andalusia retains its position as a peripheral and subordinated area.